Assessing the Sustainability Management of Djuanda Grand Forest Park in West Java, Indonesia - Khairunnisa Wizdjanul Wahyu; Rinekso Soekmadi; Hadi Susilo Arifin (Journal of Natural Resources and Environmental Management)
Djuanda Grand Forest Park, established in 1985 by Presidential Decree No. 3, is Indonesia’s first grand forest park and the largest in West Java Province, covering 528.393 hectares. The park's natural conditions support eco-tourism and environmental education. This study focuses on the sustainability of its management across four key dimensions: ecological, economic, sociocultural, and institutional. Using the Multi-Dimensional Scaling (MDS) method, data were collected from September to November 2023. The results of this research show that the ecological dimension value is 57.99% (entirely sustainable), the economic dimension value is 74.20% (entirely sustainable), the sociocultural dimension value is 32.48% (less sustainable), and the institutional dimension value is 52.80% (entirely sustainable). The overall value of the sustainability status of the Djuanda Grand Forest Park was 54.37% (entirely sustainable). The socio-cultural dimension exhibits the lowest value and is classified as less sustainable, whereas the economic dimension demonstrates the highest value and is classified as entirely sustainable.